The problems of definition of object of the crimes encroaching on ecological safety (Journal of actual problems of jurisprudence, 2019)
The problems of definition of object of the crimes encroaching on ecological safety are considered in thisarticle. The author analyzes chronologically the concept of the theory object of a crime within ecologic-legalprotection of interests. The author wants to analyse and offer the improvement of specific and direct objectof the crimes encroaching on ecological safety. The recommendations about further improvement of CC RKabout object of the crimes encroaching on ecological safety are offered.Keywords: ecology, interest, object of the crime, ecological safety, the crimes encroaching on ecologicalsafety.